La paradoja de Aquiles y la tortuga como una falacia del continuo - Mora Ramírez, Rafael Félix (2020)
In this paper analyzed the paradox of Achilles and the tortoise. To do this, start with the definition of ‘fallacy’ and ‘paradox’ and, in addition, I am putting the classification of the paradoxes established by Quine Immediately, presented the paradox of Zeno and then a way to resolve it using basic math. This solution allows me argue that the alleged paradox only was a fallacy. In the final part of this article, I show this paradox was a very special case of the fallacy of the continuity.